2017
DOI: 10.5530/fra.2017.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antioxidant Activity and Phytochemical Compositions of Celtis Tournefortii

Abstract: Context: Phytochemicals are non-nutritive plant chemicals that have protective or disease preventive properties. Because they have antioxidant property and protect our cells against oxidative damage. Aim: This work aimed to determination of phytochemical composition which total phenol content(TPC), total flavonoid content(TFC), total flavones content, alkaloid, acidity, pH, total carotenoid content, amount of carotene, β-carotene concentration, anthocyanin, amount of saponin and tannin, ascorbic acid levels, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…As regards to the TPC and TFC results, the 25% hydroalcoholic solvent revealed considerable amount of polyphenolic compounds in the extract compared to pure water and 75% ethanol. Yıldırım et al (2017) found similar results for TPC in the methanolic extract. However, TFC was higher in the present study than the results of Yıldırım et al (2017).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…As regards to the TPC and TFC results, the 25% hydroalcoholic solvent revealed considerable amount of polyphenolic compounds in the extract compared to pure water and 75% ethanol. Yıldırım et al (2017) found similar results for TPC in the methanolic extract. However, TFC was higher in the present study than the results of Yıldırım et al (2017).…”
Section: Discussionsupporting
confidence: 67%
“…due to their beneficial pharmacological effects, as they are considered safer and more reliable (Kioukia-Fougia et al 2016;Scott et al 2020). These effects could be attributed to the presence of valuable constituents (Zhang et al 2015;Keser et al 2017;Yıldırım et al 2017). In this study, antioxidant and hepatoprotective effects of C. tournefortii fruit were investigated against hepatic damage caused by Cu-toxicity in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of economic botany, Celtis tree species have great value for the activities of human livelihood. Recently, there are a large number of literatures on the economic value of Celtis species, especially for their edible fruits, and antioxidants characteristics (Yıldırım, et al, 2017). Furthermore, their durable and elastic wood is commonly used to make pulley, chopstick, spoon, cane, shovel, various tools and buildings such as agricultural tools and construction of the carving, wood is used in the making paper.…”
Section: Introductionmentioning
confidence: 99%